Kontribusi Akuntan dalam Implementasi Sustainable Development Goals (SDGs) di Indonesia - Yulita Sirinti Pongtambing; Rafika Uksi; Esther S Manapa; Eliyah A M Sampetoding; Siti Pitrianti (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
This article discusses the crucial role of accountants in supporting the achievement of Sustainable Development Goals (SDGs) in Indonesia. SDGs represent a series of global objectives aimed at enhancing societal well-being and sustainability worldwide. Accountants play a strategic role in ensuring that companies and local financial institutions comply with sustainability standards and contribute positively to the attainment of SDGs. They assist in preparing transparent and accurate sustainability reports, measuring non-financial performance, identifying sustainability-related risks, and raising awareness about SDGs among employees and stakeholders. Theoretical studies indicate that accountants can contribute to seven specific SDGs in Indonesia, including improving quality education, gender equality, decent work and economic growth, industry, innovation, and infrastructure, responsible consumption and production, climate action, and combating corruption. The research method employed is Narrative Literature Review (NLR) through Google Scholar, focusing on the relationship between the role of accountants and SDGs in Indonesia. The findings suggest that transparency in governance and integrity are key to supporting the achievement of SDGs. Accountants play a role in enhancing transparency in financial management and preventing corruption within organizations. They can also serve as role models for integrity for students and the general public. To achieve SDGs by 2030, collaboration among all parties, including accountants, local financial institutions, and professional organizations, is necessary. Innovation is required to support the role of accountants in addressing the changes towards SDGs 2030. With strong support and collaboration, it is hoped that Indonesia can achieve SDGs in a more transparent, accountable, and corruption-free manner.